Implementation of the Foundation for Instilling Religious Values in Counseling Guidance Services at Madrasah Tsanawiyah - Elfidayati Elfidayati; Saiful Akhyar Lubis; Nurussakinah Daulay (STAI Hubbulwathan Duri, 2022)
The importance of education is very consistent in the fields of science and culture, Islam has its own teachings in the field of education, and Islamic education is to realize the ideal image of Muslims. Therefore, the education theory that is built must be sourced from Islamic education. Because all references or references from which emanate values and knowledge will be internalized in Islamic education. The process of formal Islamic education came only after the revival of madrasas. In this study, the author uses field research (field research) which is a mixed-method research method with a phenomenological approach, (examining the facts of what happened) where the author focuses more on describing a phenomenon or event that is obtained with the background of the researcher's interest in a phenomenon. Students at MTsN 1 Langkat 1 Langkat. Based on the data, in the 4-year academic year before the pandemic and until the initial meeting, it was found that in the 2020/2021 academic year as many as 256 or 28% of students, students experienced the following problems: violation of school rules, student attendance, lazy learning, brawls, pornography, disturbing friends, learning difficulties in learning, feelings of inferiority, fear of being wrong/ Lack of confidence and lack of serious learning awareness. This madrasa is still very much needed by parents who show their desire to send their children to a better education through the program -programs that shape early adolescent development.